Case Report: Transforming small cell lung cancer: two cases report and literature review - Liu, Jinlong; Ai, Jing; Zhao, Lize; Qian, Yimeng; Zhao, Qingxin; Ma, Chunling; Zhao, Yu; Zhao, Jing (Frontiers in Oncology, 2025)
Transformation of non-small cell lung cancer (NSCLC) to small cell lung cancer (SCLC) is a relatively rare event with an incidence of about 3%-14%. Due to the poor treatment outcomes and prognosis associated with this transformation, understanding its underlying mechanisms is crucial for improving the diagnosis, management, and prognosis of transformed small cell lung cancer (T-SCLC). In this paper, we present two cases of T-SCLC and review the molecular mechanisms, clinical features, and treatment strategies post-transformation. We emphasize the importance of considering pathological transformation in cases of resistance to NSCLC treatment, monitoring changes in tumor markers, and conducting a re-biopsy. Finally, we propose effective treatment measures for managing T-SCLC.